CLONING OF cDNA-GENES OF ARABIDOPSIS THALIANA TRANSLATION INITIATION FACTOR 2 α-, β-, and γ-SUBUNITS, THEIR EXPRESSION IN ESCHERICHIA COLI AND ISOLATION OF RECOMBINANT PROTEINS AteIF2α, AteIF2β, AteIF2γ - Zhigailov , A.V.; Stanbekova , G.E.; Beisenov , D.K.; Kislitsin , V.U.; Alexandrova , A.M.; Krasnoshtanov , V.K.; Iskakov , B.K. (Eurasian Journal of Applied Biotechnology, 2018)
The eukaryotic translation initiation factor 2 (eIF2) consists of three non-identical subunits, denoted α, β and γ; α-subunit performs a regulatory function. This factor is strictly required for initiation of eukaryotic mRNA translation. In animal cells, phosphorylation of the α-subunit of the meIF2 factor by specific kinases dramatically inhibits the initiation of translation of the majority of mRNAs during various stresses. In plants, the role of phosphorylation of homologous factor (peIF2α) in regulation of protein biosynthesis remains unclear. The cDNA genes of α, β and γ subunits of eIF2 factor from A. thaliana were amplified by RT-PCR (AteIF2α, AteIF2β and AteIF2γ, respectively). These cDNA genes were cloned in E. coli cells in the expression vector pET19b. Recombinant proteins AteIF2α, AteIF2β and AteIF2γ were isolated by affinity chromatography, dialyzed and concentrated. They all had correct dimensions. These preparations were used to assemble a full factor of three recombinant subunits. At ionic strength corresponding to 100 mM KCl, the subunits could form united, but not stable complex, which dissociated already at 150 mM, whereas the native factor can remain stable even at 350 mM KCl. The assembly of plant factor from individual subunits makes it possible to elucidate the role of peIF2α phosphorylation in regulation of various mRNAs translation in plant in vitro system and also in the in vivo system permits constructing cellular factor peIF2 from various modified subunits